1983
DOI: 10.1254/jjp.33.349
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic action of glucocorticoids in rats.

Abstract: Abstract-The effects of three glucocorticoids (steroids: hydrocortisone, prednisolone and dexamethasone)on IgE antibody-mediated immediate hypersensitivity reactions in rats were studied.Forty-eight hr homologous passive cutaneous anaphylaxis (PCA) was inhibited in a dose response manner by the administration of steroids 2 hr prior to challenge.When steroids were administered at various times before challenge, each steroid showed different patterns of time courses for inhibition of homologous PCA. Maximum inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…We also confirmed that a time lag is essential for these actions of GCs. On the other hand, it is in teresting that the inhibition of PCA by Hydro and Pred was biphasic as reported previously (16). Furthermore, biphasic actions of Hydro and Pred were also observed in TAT activity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We also confirmed that a time lag is essential for these actions of GCs. On the other hand, it is in teresting that the inhibition of PCA by Hydro and Pred was biphasic as reported previously (16). Furthermore, biphasic actions of Hydro and Pred were also observed in TAT activity.…”
Section: Discussionsupporting
confidence: 85%
“…In 1983, Nagai et al (16) suggested the possibility that a protein synthesis-independent mechanism is in volved in the anti-allergic action of GC in rats. We also indicated that IgE antibody-mediated passive cutaneous anaphylaxis (PCA) in rats, an important immediate hypersensitivity reaction model, is inhibited by GC, and that inhibition of vascular permeability increase plays an important part in the inhibition of PCA (17).…”
mentioning
confidence: 99%
“…All these results suggest that mouse ear PCA might be a useful method for evaluating antianaphylactic agents like rat homologous PCA in the back skin [1][2][3].…”
mentioning
confidence: 87%
“…In the ear, PCA reaction was more sensitive and reproducible than that in the dorsal skin. The reaction was significantly suppressed by ketotifen, one of antianaphylactic agents.Passive cutaneous anaphylaxis (PCA) reaction [9] is one of the most useful methods for evaluating anti anaphylactic agents [1][2][3]. In mice, PCA reaction was usually elicited in dorsal skin and the activity of antianaphylactic agents was evaluated by means of reduced dimension or diameter of PCA site [4], In our preliminary experiment, however, the PCA reaction in dorsal skin of mice was little reproducible.…”
mentioning
confidence: 99%
“…These results suggest a possibility that the vascular permeability inhibitory protein plays an important role in the inhibition of the PCA and the skin reactions observed in the pres ent study. However, Nagai et al [ 10] indicated that the IgE antibody-mediated rat homologous PCA is inhi bited by glucocorticoids with a latent period of about 1 h but that antiglucocorticoids [24, 30] do not influ ence the inhibition. Furthermore, a protein synthesis inhibitor, actinomycin D, also failed to recover the in hibition of the rat homologous PCA [unpubl.…”
Section: Discussionmentioning
confidence: 99%